Educational strategies to reduce risk: a choice of social responsibility - Federica La Longa; Romano Camassi; Massimo Crescimbene (Annals of Geophysics, 2012)
This study develops the critical reflections of the activities for information, training and education that have been conducted by a group of researchers of the Istituto Nazionale di Geofisica e Vulcanologia in recent years. In particular, from an epistemological point of view, our analysis involves: (i) science outreach, the link between science and the world; (ii) science teaching and its role in the contact between science and schools; and (iii) risk education, seen as a process that can develop a culture of risk in relation to the territory in which we live. These issues are critically analyzed on the basis of experience gained since 1995. The educational methodologies tested in ‘peacetime’ (in the absence of seismic events) with the EDURISK Project are compared with those experienced during an emergency in Abruzzo, Italy. Today, we increasingly refer to prevention as the primary strategy of defense against risk. However, very often the responsibility of prevention falls on others, such as the government, institutions and/or local authorities. The citizens then perceive themselves as powerless against the inevitability of natural events, and they refer to these ‘rulers’ for the implementation of effective prevention policies. So, as researchers, what are the most effective actions we can take to influence risk reduction and to motivate the choices of the people? Must the effectiveness of our interventions be based on scientific information or on specific training, or must it be reached through the development of values, actions and awareness? Must our interventions be oriented and developed to inform, to train or to educate?